Urbanización regional y asentamientos irregulares. Caso de la ciudad de Huamantla, Tlaxcala, México - Hernández Hernández, Daniel (2024)
Fil: Hernández Hernández, Daniel. Colegio de Tlaxcala (COLTLAX); México.